Are they worth it? – An evaluation of predictions for NBA `Fantasy Sports' - Jörg Döpke; Tim Köhler; Lars Tegtmeier (Journal of Economics and Finance, 2023)
Fantasy Sports' - an internet-based game in which participants chose virtual teams of real professional athletes - has recently gained in popularity. Various firms provide projections regarding athletes' future performance to help participants choose their virtual teams. We evaluate such forecasts based on 1658 projections regarding NBA basketball of four selected projection providers that were collected in February 2022. We calculate standard measures of forecast quality and find that the use of professional forecasts reduces the errors made in naïve forecasts, but only to a moderate extent. Applying regression-based tests of forecast efficiency, we find that the predictions are inefficient and, in some cases, even biased. Third, pairwise comparisons of the accuracy of the providers suggest notable differences among such providers in the short run. We use a simple optimization algorithm to choose a virtual team for each match day and feed it with the forecasts of the providers. Subsequently, we rank the providers according to the score obtained by these teams. We find small, although in one case significant, long-run differences between the providers, among whom each provides better accuracy than that of a naïve projection based on these athletes' past performances. Finally, we simulate one-on-one competition among various forecast providers to ascertain the long-term profitability of their services. Given the small magnitude of the detected differences, our results, in brief, raise doubts as to whether the forecasts provided are worth the money.
Keywords: C53; G14; L83; 330; Forecast evaluation; Information efficiency; Sport